Assessment of Health Behaviors Related to Nutrition of Pregnant Women in Hospitals - Rasha Shehab Ahmed,; Hanaa Hussein Mukhlif, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study aims to assess the behaviors of pregnant women regarding their nutritional status in hospitals within Mosul City to promote optimal nutrition during pregnancy. The study used a descriptive design from December 2023 to April 2024. A purposive sample of pregnant women who visited hospitals in Mosul was collected. The study tool consisted of demographic data about pregnant women, six questions about women's health histories, and seven questions about health behaviors related to nutrition, with four choices for each question. And eating meat during one week. Seven experts measured the tool and its reliability (0.81). Most of the women (63.6%) reported taking supplements, and (66.4%) were in the third trimester. A small percentage of women (15.6%) reported having a deformity. The majority of women (81.6%) reported having visited a healthcare center. The majority of women (72.8%) had 1-3 pregnancies. Most pregnant women never eat meat, fish, or dairy during the week. The study revealed that a significant number of pregnant women in the sample reported taking supplements and eating meat types and dairy are lower. The study recommended appropriate nutritional guidance be provided to pregnant women in health centers. تهدف هذه الدراسة إلى تقييم سلوكيات النساء الحوامل فيما يتعلق بحالتهن التغذوية في المستشفيات داخل مدينة الموصل لتعزيز التغذية المثالية أثناء الحمل. الطرق: استخدمت الدراسة تصميماً وصفياً من كانون الأول 2023 إلى نيسان 2024. تم جمع عينة هادفة من النساء الحوامل اللواتي زارن المستشفيات في الموصل. تكونت أداة الدراسة من البيانات الديموغرافية عن النساء الحوامل، وستة أسئلة حول التاريخ الصحي للمرأة، وسبعة أسئلة حول السلوكيات الصحية المرتبطة بالتغذية، بواقع أربعة اختيارات لكل سؤال. وتناول اللحوم خلال أسبوع واحد. قام سبعة خبراء بقياس الأداة ومدى موثوقيتها (0.81). أبلغت معظم النساء (63.6%) عن تناول المكملات الغذائية، و(66.4%) كن في الثلث الثالث من الحمل. وأفادت نسبة صغيرة من النساء (15.6%) بوجود تشوه. وأفادت غالبية النساء (81.6%) بأنهن قمن بزيارة أحد مراكز الرعاية الصحية. غالبية النساء (72.8٪) حصلن على 1-3 حالات حمل. لا تأكل معظم النساء الحوامل اللحوم أو الأسماك أو منتجات الألبان أبدًا خلال الأسبوع. كشفت الدراسة أن عدداً كبيراً من النساء الحوامل في العينة أفادنا بأن تناول المكملات الغذائية وتناول أنواع اللحوم والألبان أقل. وأوصت الدراسة بتقديم الإرشاد الغذائي المناسب للنساء الحوامل في المراكز الصحية